2021
DOI: 10.3390/biomedicines9020144
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Rice Bran-Modified Human Gut Microbial Consortia Confers Protection against Colon Carcinogenesis Following Fecal Transfaunation

Abstract: Rice bran, removed from whole grain rice for white rice milling, has demonstrated efficacy for the control and suppression of colitis and colon cancer in multiple animal models. Dietary rice bran intake was shown to modify human stool metabolites as a result of modifications to metabolism by gut microbiota. In this study, human stool microbiota from colorectal cancer (CRC) survivors that consumed rice bran daily was examined by fecal microbiota transplantation (FMT) for protection from azoxymethane and dextran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 60 publications
(81 reference statements)
2
21
0
Order By: Relevance
“…For patients with colon cancer, antibiotic therapy is even recommended as an immunotherapy strategy [ 100 , 101 ]. After antibiotic manipulation of the gut microbiota, a reduction in tumor load was detected, which supported the hypothesis of bacterial involvement in carcinogenesis [ 102 ]. For example, metronidazole can eradicate Fusobacterium colonization and inhibit the proliferation of CRC [ 103 ].…”
Section: Effect Of Antibioticssupporting
confidence: 58%
“…For patients with colon cancer, antibiotic therapy is even recommended as an immunotherapy strategy [ 100 , 101 ]. After antibiotic manipulation of the gut microbiota, a reduction in tumor load was detected, which supported the hypothesis of bacterial involvement in carcinogenesis [ 102 ]. For example, metronidazole can eradicate Fusobacterium colonization and inhibit the proliferation of CRC [ 103 ].…”
Section: Effect Of Antibioticssupporting
confidence: 58%
“…26 Notably, germfree mice receiving human fecal transplantation with rice-bran modified stool microbes showed significantly less colon cancerous lesions compared to mice humanized by stool microbes from control fed adults (without rice-bran intervention). 27 Taken together, these studies provided convincing rationale for testing the hypothesis that RB and Bifidobacterium-fermented rice bran (FRB) can restructure the "high risk" or dysbiotic gut microbiota toward the colonization of microbial communities that protect against CRC growth and progression. However, the microbiomemediated and microbiota-independent colonic tissue/tumor effects and metabolic pathways impacted following dietary RB or FRB remain largely unknown.…”
Section: Introductionmentioning
confidence: 98%
“…The mice were transfaunated with rice bran-modified microbiota collected from human stool during fecal microbiota transplant. The results showed that TMAO and tartrate, being associated with CRC development, were reduced in murine colon tissues [40]. Nevertheless, these findings may vary under different circumstances.…”
Section: Discussionmentioning
confidence: 81%